Continuous operation in an electric and hydrogen hybrid energy storage system for renewable power generation and autonomous emergency power supply. (30th August 2019) - Zhang, Z.; Sato, K.; Nagasaki, Y.; Tsuda, M.; Miyagi, D.; Komagome, T.; Tsukada, K.; Hamajima, T.; Ishii, Y.; Yonekura, D.
Abstract: Under the background of extensive improvement of renewable resources and demand for reliable emergency power supply, we proposed a hybrid energy storage system including an electric double-layer capacitor bank and a hydrogen system which is composed of fuel cell, electrolyzer, gas tank and metal hydride tank. Through its integration with photovoltaic power sources in a local direct current grid, we expect to obtain both of stable energy source at ordinary times and long-time reliable autonomous emergency power supply when outages happen. A three-day demonstration of the proposed system was performed. The fluctuation compensation performance of the components and the long-time stable power supply obtained by the entire system were evaluated at first, hence the configuration and the management methods of the proposed system were verified in the autonomous emergency power supply application. Meanwhile, the performance of the hybrid use of the gas tank and the metal hydride tank in the system was preliminarily evaluated, for its effectiveness verification on reducing auxiliary power for temperature condition of the metal hydride tank. Moreover, we investigated the distribution characteristics of the power and energy loss in the electric double-layer capacitor, electrolyzer and fuel cell, and their correlation to the efficiency characteristics under different conditions during the operation. The investigation results showed that the continual low-load-ratio state of the electrolyzer and fuel cell led to the low efficiency, the rare high-power occurrence of the electrolyzer and fuel cell led their demanded excessive power capacity. Thus, we proposed a solution method of shifting the electrolyzer and fuel cell's load to the EDLC, when the electrolyzer and fuel cell are in low-load-ratio and excessive high-power state, in order for efficiency increase and facility capacity reduction. Highlights: Proposed a hydrogen storage composed of gas tank and metal hydride tank in series. Realized 72-hour demonstration of an electric and hydrogen energy storage system. Verified system's ability of reliable long-time autonomous emergency power supply. Clarified electrolyzer and fuel cell's low efficiency and excessive capacity issue. Proposed solution method of load shift from electrolyzer and fuel cell to EDLC.